Local power and violence in the Andes: A case in Abancay at the end of the 18th century - Garzón Rivera, Emilio (1991)
The analysis of the mechanisms of local power in the Andean area constitutes one of the great tasks that historiography still has pending for the colonial period. The importance of corregidores, priests and caciques in rural areas has been highlighted in numerous historical, ethnological and even anthropological works, but the study of the relationships between them, within what is called local power, and the reasons for conflict and forms of social, economic and political control of the peasant population still require the effort of social science researchers to explain and understand them more deeply.